Composite additive for electrolytic copper foil, preparation method of electrolytic copper foil and electrolytic copper foil
By optimizing the proportion of composite additives, the performance and cost problems in the production of extremely thin electrolytic copper foils are solved, and copper foil preparation with high tensile strength and elongation is achieved, which improves production efficiency and product quality.
Patent Information
- Application Number
- CN202411364338.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to improve the yield and reduce costs while meeting the performance requirements of extremely thin electrolytic copper foils. The additive control mechanism is unclear, which affects the appearance and mechanical properties of the copper foil.
An aqueous solution composite additive system is adopted, including agent A, agent B, agent C and agent D. By studying their interaction mechanism, the additive ratio is optimized, and electrolytic copper foil with high tensile strength and elongation is prepared.
The appearance and mechanical properties of copper foil are improved, the surface roughness and production costs are reduced, and the quality and production efficiency of extremely thin copper foil are improved.
Smart Images

Figure CN119243269A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to electrolytic copper foil, and in particular to a composite additive for electrolytic copper foil, a method for preparing the electrolytic copper foil, and the electrolytic copper foil. Background Art
[0002] Electrolytic copper foil, as a carrier of active substances and a collector of negative electrode electrons, is the basic raw material for the preparation of lithium-ion batteries. The various performance properties of its products are closely related to the capacity, efficiency, safety performance and life of lithium-ion batteries. In order to achieve higher battery energy density, lithium battery copper foil needs to develop in a lighter and thinner direction, while taking into account the safety performance of the battery. Therefore, performance requirements such as higher tensile strength, higher elongation, lower resistivity and low profile are also proposed for copper foil.
[0003] However, thinner electrolytic copper foil has extremely high requirements for production conditions. If the foil is extremely thin and has higher performance, the production difficulty increases significantly. The harsh production conditions and the increase in problems in the production process lead to low yields of extremely thin and high-performance electrolytic copper foil, increased production costs, and reducing consumption in the copper foil manufacturing process and improving the quality of copper foil are still difficult problems to be solved.
[0004] In the sulfuric acid-copper sulfate system, additives play a decisive role in the appearance quality and mechanical properties of copper foil. A small fluctuation in the proportion of additives in the electrolyte will cause significant changes in the various indicators of electrolytic copper foil. However, the additive regulation mechanism is still unclear, and no clear guidance and regulation can be made for the production and manufacturing process of electrolytic copper foil. Therefore, it is very important to explore new composite additives and their production regulation mechanism for electrolytic copper foil to promote the various properties of electrolytic copper foil to a higher level.
[0005] Therefore, a composite additive for electrolytic copper foil and a method for preparing the electrolytic copper foil are proposed to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a composite additive for electrolytic copper foil, a method for preparing electrolytic copper foil and the electrolytic copper foil. The present invention focuses on exploring the interaction mechanism between the new composite additive and its components, studying the synergistic or antagonistic effect in the electrolysis process, and exploring the optimal composite additive ratio according to the additive action mechanism under standardized electrolysis process parameters to obtain a copper foil with good appearance and mechanical properties.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a composite additive for electrolytic copper foil, characterized in that the composite additive is an aqueous solution, including agent A, agent B, agent C, and agent D, wherein agent A is sodium hydroxymethane sulfonate or sodium 3-mercaptopropane sulfonate or sodium N or N-alcoholthiopropane sulfonate or one or more of the four, agent B is fish glue or polyethyleneimine or polyacrylamide or one or more of the three, agent C is polyoxyethylene polypropylene ether or polypropylene glycol or cyclopentyl methyl ether or one or more of the three, and agent D is HG water-soluble additive.
[0008] As a preferred technical solution of the present invention, the concentration of agent A is 5-20 ppm, the concentration of agent B is 20-50 ppm, the concentration of agent C is 5-10 ppm, and the concentration of agent D is 2-20 ppm.
[0009] A method for preparing an electrolytic copper foil, characterized in that it comprises the following steps:
[0010] Step 1): Put the copper material into a tank containing sulfuric acid, fill the tank with air through a fan, and dissolve the copper to form a copper sulfate electrolyte;
[0011] Step 2): After multi-stage filtration and purification and temperature adjustment by a heat exchanger, the copper ion concentration, sulfuric acid concentration and electrolyte temperature in the copper sulfate electrolyte reach the specified conditions;
[0012] Step 3): injecting the composite additive and chloride ions described in claim 1 into a qualified copper sulfate electrolyte, maintaining the concentration of each component of the composite additive, electrolyzing to obtain copper foil, and then placing the copper foil in an environment of 50° C. to 80° C. for 30 hours.
[0013] As a preferred technical solution of the present invention, the copper sulfate electrolyte has a copper ion content of 95 to 105 g / L, a sulfuric acid content of 80 to 90 g / L, and a chloride ion content of 10 to 35 mg / L.
[0014] As a preferred technical solution of the present invention, the copper sulfate electrolyte has: electrolyte temperature: 50-54°C, current density: 55-75A / dm2.
[0015] As a preferred technical solution of the present invention, the thickness of the lithium battery copper foil is 4.5-6 μm.
[0016] An electrolytic copper foil, characterized in that it comprises the preparation method described in any one of claims 3 to 6, wherein the crystal state of the electrolytic copper foil is granular crystals, the surface roughness is ≤1.5 μm, the glossiness is ≥150, the tensile strength (140°C, 15 min) is ≥400 MPa, and the elongation (140°C, 15 min) is ≥8%.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. This scheme adopts a new composite additive system, and the components are properly matched and used in small amounts. During the experiment, the new composite additive and the interaction mechanism between the components are explored. Under the standardized electrolysis process parameters, the optimal composite additive ratio is explored based on their synergistic or antagonistic effects to produce copper foil with good appearance and mechanical properties.
[0019] 2. This scheme introduces sodium N,N-methylthiopropane sulfonate into the electrolytic copper foil additive to form a complex with chloride ions, which will reduce the reduction of copper ions to cuprous ions, intensify the polarization effect of the additive system, promote the refinement of the surface grain size, and reduce the surface roughness. At the same time, the copper crystals on the copper foil surface grow mainly along the (111) crystal plane, and the (200) and (220) crystal planes compete for growth, thereby improving the mechanical properties of the copper foil.
[0020] 3. This scheme introduces polyoxyethylene polypropylene ether, which has a high hydrophilic-lipophilic balance and good solubility. When it is combined with sodium 3-mercaptopropane sulfonate to form an additive formula, sodium 3-mercaptopropane sulfonate can be dissolved in the core formed by polyoxyethylene polypropylene ether, which synergistically promotes the leveling and bright performance of the copper foil coating. Sodium N,N-alcoholthiopropane sulfonate can be used as a brightener for electrolytic copper foil, and when used in combination with a surfactant, it can improve the brightness and ductility of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM photo of the matte surface of the copper foil prepared in Example 1, 2, 3 or 4 of the present invention;
[0022] Figure 2 This is a SEM photograph of the rough surface of the copper foil prepared in Comparative Example 1, 2, 3 or 4 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The invention provides a technical solution: a composite additive for electrolytic copper foil, characterized in that it comprises an agent A, an agent B, an agent C and an agent D, wherein the agent A is one or more of sodium hydroxymethyl sulfonate, sodium 3-mercaptopropane sulfonate or sodium N,N-alcoholthiopropane sulfonate, and the concentration of the agent A is 5-20 ppm, the agent B is one or more of fish glue, polyethylene imine or polyacrylamide, and the concentration of the agent B is 20-50 ppm, the agent C is one or more of polyoxyethylene polypropylene ether, polypropylene glycol or cyclopentyl methyl ether, and the concentration of the agent C is 5-10 ppm, and the agent D is an HG water-soluble additive, and the concentration of the agent D is 2-20 ppm.
[0025] The copper material is put into a tank with sulfuric acid, and the tank is filled with air through a fan to dissolve the copper to form a copper sulfate electrolyte; after multi-stage filtration and purification and temperature adjustment by a heat exchanger, the copper ion concentration, sulfuric acid concentration and electrolyte temperature in the copper sulfate electrolyte reach the specified conditions; the copper ion content in the copper sulfate electrolyte is 95-105g / L, the sulfuric acid content is 80-90g / L, the chloride ion content is 10-35mg / L, the electrolyte temperature of the copper sulfate electrolyte is 50-54°C, the current density is 55-75A / dm2, and the thickness of the lithium battery copper foil is 4.5-6μm; finally, the composite additive and chloride ion are injected into the qualified copper sulfate electrolyte, the concentration of each component of the composite additive is maintained, the copper foil is obtained by electrolysis, and then the copper foil is placed in an environment of 50°C to 80°C for 30h.
[0026] The crystal state of the electrolytic copper foil is granular crystal, with surface roughness ≤1.5μm, gloss ≥150, tensile strength (140℃, 15min) ≥400MPa, and elongation (140℃, 15min) ≥8%.
[0027] Example 1
[0028] The copper sulfate electrolyte prepared by dissolving the copper material has a Cu2+ concentration of 95g / L, a H2SO4 concentration of 85g / L, a chloride ion concentration of 32.5ppm, an electrolyte temperature of 53°C, an electrolyte flow rate of 57.5m3 / h, and a current density of 70A / dm2. The A agent sodium hydroxymethyl sulfonate is maintained at 16ppm, the B agent fish glue is 34ppm, the C agent polypropylene glycol is 6ppm, and the D agent HG is 11ppm. The 6μm copper foil is electrolyzed and placed in an environment of 80°C for 30h. It is confirmed that the crystal state of the copper foil is granular crystal, and its surface roughness Rz value is 1.33μm, the glossiness (Gs(60°)) is 178, the tensile strength (140°C, 15min) is 424.34MPa, and the elongation (140°C, 15min) is 9.04%.
[0029] Comparative Example 1
[0030] The copper sulfate electrolyte prepared by dissolving the copper material has a Cu2+ concentration of 95g / L, a H2SO4 concentration of 85g / L, a chloride ion concentration of 32.5ppm, an electrolyte temperature of 53°C, an electrolyte flow rate of 57.5m3 / h, and a current density of 70A / dm2. The A agent sodium hydroxymethyl sulfonate is maintained at 16ppm, the B agent fish glue is 29ppm, the C agent polypropylene glycol is 6ppm, and the D agent HG is 3ppm. The 6μm copper foil is electrolyzed and placed in an environment of 80°C for 30h. It is confirmed that the crystal state of the copper foil is granular crystal, and its surface roughness Rz value is 1.51μm, the glossiness (Gs(60°)) is 168, the tensile strength (140°C, 15min) is 389.24MPa, and the elongation (140°C, 15min) is 6.04%.
[0031] Example 2
[0032] The copper material was dissolved to prepare a copper sulfate electrolyte, in which the concentration of Cu2+ in the electrolyte was 95g / L, the concentration of H2SO4 was 85g / L, the concentration of chloride ions was 32.5ppm, the electrolyte temperature was 53°C, the electrolyte flow rate was 57.5m3 / h, and the current density was 70A / dm2. The A agent was 16ppm of sodium 3-mercaptopropane sulfonate, the B agent was 31ppm of polyethyleneimine, the C agent was 6ppm of polyoxyethylene polypropylene ether, and the D agent was 13ppm. The 6μm copper foil was electrolyzed and placed in an environment of 80°C for 2 days. It was confirmed that the crystal state of the copper foil was granular crystals, and its surface roughness Rz value was 1.42μm, the glossiness (Gs(60°)) was 166, the tensile strength (140°C, 15min) was 448.45MPa, and the elongation (140°C, 15min) was 9.41%
[0033] Comparative Example 2
[0034] The copper material was dissolved to prepare a copper sulfate electrolyte, in which the concentration of Cu2+ in the electrolyte was 95g / L, the concentration of H2SO4 was 85g / L, the concentration of chloride ions was 32.5ppm, the electrolyte temperature was 53°C, the electrolyte flow rate was 57.5m3 / h, and the current density was 70A / dm2. The A agent was 14ppm of sodium 3-mercaptopropane sulfonate, the B agent was 31ppm of polyethyleneimine, the C agent was 6ppm of polyoxyethylene polypropylene ether, and the D agent was 2ppm. A 6μm copper foil was obtained by electrolysis and placed in an environment of 80°C for 2 days. It was confirmed that the crystal state of the copper foil was granular crystals, and its surface roughness Rz value was 1.33μm, the glossiness (Gs(60°)) was 155, the tensile strength (140°C, 15min) was 379.18MPa, and the elongation (140°C, 15min) was 6.35%
[0035] Example 3
[0036] The copper material was dissolved to prepare a copper sulfate electrolyte, in which the concentration of Cu2+ in the electrolyte was 95g / L, the concentration of H2SO4 was 85g / L, the concentration of chloride ions was 32.5ppm, the electrolyte temperature was 53°C, the electrolyte flow rate was 57.5m3 / h, and the current density was 60A / dm2. A 14ppm sodium hydroxymethyl sulfonate agent, a 34ppm fish glue agent, a 6ppm polypropylene glycol agent, and a 12ppm HG agent were maintained. A 4.5μm copper foil was obtained by electrolysis and placed in an environment of 70°C for 30h. It was confirmed that the crystal state of the copper foil was granular crystals, and its surface roughness Rz value was 1.36μm, the glossiness (Gs(60°)) was 152, the tensile strength (140°C, 15min) was 432.76MPa, and the elongation (140°C, 15min) was 8.47%
[0037] Comparative Example 3
[0038] The copper material was dissolved to prepare a copper sulfate electrolyte, in which the concentration of Cu2+ in the electrolyte was 95g / L, the concentration of H2SO4 was 85g / L, the concentration of chloride ions was 32.5ppm, the electrolyte temperature was 53°C, the electrolyte flow rate was 57.5m3 / h, and the current density was 60A / dm2. A 16ppm sodium hydroxymethyl sulfonate agent, a 27ppm fish glue agent, a 6ppm polypropylene glycol agent, and a 3ppm HG agent were maintained. A 4.5μm copper foil was obtained by electrolysis and placed in an environment of 70°C for 30h. It was confirmed that the crystal state of the copper foil was granular crystals, and its surface roughness Rz value was 1.65μm, the glossiness (Gs(60°)) was 171, the tensile strength (140°C, 15min) was 377.23MPa, and the elongation (140°C, 15min) was 5.18%
[0039] Example 4
[0040] The copper material was dissolved in a copper sulfate electrolyte, in which the concentration of Cu2+ was 95g / L, the concentration of H2SO4 was 85g / L, the concentration of chloride ions was 32.5ppm, the electrolyte temperature was 53°C, the electrolyte flow rate was 57.5m3 / h, and the current density was 60A / dm2. The A agent was 14ppm of sodium 3-mercaptopropane sulfonate, the B agent was 31ppm of polyethyleneimine, the C agent was 6ppm of polyoxyethylene polypropylene ether, and the D agent was 11ppm. The 4.5μm copper foil was electrolyzed and placed in an environment of 70°C for 30h. It was confirmed that the crystal state of the copper foil was granular crystals, and its surface roughness Rz value was 1.46μm, the glossiness (Gs(60°)) was 158, the tensile strength (140°C, 15min) was 429.83MPa, and the elongation (140°C, 15min) was 8.25%
[0041] Comparative Example 4
[0042] The copper sulfate electrolyte prepared by dissolving the copper material has a Cu2+ concentration of 95g / L, a H2SO4 concentration of 85g / L, a chloride ion concentration of 32.5ppm, an electrolyte temperature of 53°C, an electrolyte flow rate of 57.5m3 / h, and a current density of 60A / dm2. The A agent is 13ppm of sodium 3-mercaptopropane sulfonate, the B agent is 29ppm of polyethyleneimine, and the C agent is 6ppm. The 4.5μm copper foil is electrolyzed and placed in an environment of 70°C for 30h. It is confirmed that the crystal state of the copper foil is granular crystal, and its surface roughness Rz value is 1.57μm, the glossiness (Gs(60°)) is 133, the tensile strength (140°C, 15min) is 367.15MPa, and the elongation (140°C, 15min) is 3.24%.
[0043] The addition amount of the composite additive, copper foil specifications and mechanical properties in the above examples are shown in the following table.
[0044]
[0045]
[0046] In summary, by means of the above technical solution of the present invention, by adopting the above new composite additive and optimizing its ratio, this formula can promote grain refinement, reduce copper foil defects, and produce copper foil with high tensile strength and good elongation. The electrolyte of the present invention is suitable for producing 4.5 micron-6 micron ultra-thin copper foil, and the prepared copper foil has excellent mechanical properties, good appearance, and easy to control glossiness.
[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite additive for electrolytic copper foil, characterized in that: The composite additive is an aqueous solution, including agent A, agent B, agent C, and agent D. The agent A is sodium hydroxymethane sulfonate or sodium 3-mercaptopropane sulfonate or sodium N or N-alcoholthiopropane sulfonate or one or more of the four. The agent B is fish glue or polyethyleneimine or polyacrylamide or one or more of the three. The agent C is polyoxyethylene polypropylene ether or polypropylene glycol or cyclopentyl methyl ether or one or more of the three. The agent D is an HG water-soluble additive.
2. The composite additive for electrolytic copper foil according to claim 1, characterized in that: The concentration of agent A is 5-20 ppm, the concentration of agent B is 20-50 ppm, the concentration of agent C is 5-10 ppm, and the concentration of agent D is 2-20 ppm.
3. A method for preparing an electrolytic copper foil, characterized in that: The following steps are involved: Step 1): Put the copper material into a tank containing sulfuric acid, fill the tank with air through a fan, and dissolve the copper to form a copper sulfate electrolyte; Step 2): After multi-stage filtration and purification and temperature adjustment by a heat exchanger, the copper ion concentration, sulfuric acid concentration and electrolyte temperature in the copper sulfate electrolyte reach the specified conditions; Step 3): injecting the composite additive and chloride ions described in claim 1 into a qualified copper sulfate electrolyte, maintaining the concentration of each component of the composite additive, electrolyzing to obtain copper foil, and then placing the copper foil in an environment of 50° C. to 80° C. for 30 hours.
4. The method for preparing an electrolytic copper foil according to claim 3, characterized in that: The copper sulfate electrolyte has a copper ion content of 95-105 g / L, a sulfuric acid content of 80-90 g / L, and a chloride ion content of 10-35 mg / L.
5. The method for preparing an electrolytic copper foil according to claim 3, characterized in that: The copper sulfate electrolyte: electrolyte temperature: 50-54°C, current density: 55-75A / dm2.
6. The method for preparing an electrolytic copper foil according to claim 3, characterized in that: The lithium battery copper foil has a thickness of 4.5-6 μm.
7. An electrolytic copper foil, characterized in that: The preparation method comprising any one of claims 3-6, wherein the crystal state of the electrolytic copper foil is granular crystals, the surface roughness is ≤1.5μm, the glossiness is ≥150, the tensile strength (140℃, 15min) is ≥400MPa, and the elongation (140℃, 15min) is ≥8%.
Citation Information
Cited By
Preparation and detection method of electrolytic copper foil with low roughness and high binding force
CN121295274A
